Infants lost in (peripersonal) space? - Bremner, A; Holmes, N; Spence, C (2008)
A significant challenge in developing spatial representations for the control of action is one of multisensory integration. Specifically, we require an ability to efficiently integrate sensory information arriving from multiple modalities pertaining to the relationships between the acting limbs and the nearby external world (i.e. peripersonal space), across changes in body posture and limb position. Evidence concerning the early development of such spatial representations points towards the independent emergence of two distinct mechanisms of multisensory integration. The earlier-developing mechanism achieves spatial correspondence by representing body parts in their typical or default locations, and the later-developing mechanism does so by dynamically remapping the representation of the position of the limbs with respect to external space in response to changes in postural information arriving from proprioception and vision.